ANALYSIS OF NOISE IMMUNITY OF RECEPTION OF SIGNALS WITH MULTIPLE PHASE SHIFT KEYING UNDER THE INFLUENCE OF SCANNING INTERFERENCE - G. V. Kulikov; N. V. Dung (Российский технологический журнал, 2018)
Signals with multi-phase shift keying (M-PSK) have long been successfully used in digital information transmission systems with high bandwidth. Their use is regulated by various communication standards. The noise immunity characteristics of their reception against the background of white Gaussian noise are well studied. The article deals with the case when, at the input of the receiver, besides noise, there is a scanning interference. The noise immunity of signal reception with multi-phase shift keying in the presence of noise and scanning interference was analyzed using statistical radio engineering methods. In this case, the interference is represented as a harmonic interference with a frequency varying according to the sawtooth law. Two cases are considered in the study. The first is when the scanning interference does not fall into the zone of the main lobe of the signal spectrum. In this case, its influence is negligible, and it practically does not change the noise immunity of the reception. The second case, when the frequency range of the scan coincides with the zone of the main lobe of the signal spectrum, is more dangerous. The dependences of the probability of a bit error on the deviation frequency of the scanning interference, its intensity and the signal-to-noise ratio are obtained. It is shown that the noise immunity of receiving signals with multi-phase shift keying deteriorates greatly in the presence of scanning interference falling in the region of the main lobe of the spectrum of the useful signal, and this effect is greatly enhanced with increasing signal positionality. When changing the frequency deviation of such interference, its effect on the noise immunity of the M-PSK demodulator changes only slightly. To increase the noise immunity of receiving signals against the background of scanning interference, it is necessary to use interference compensation algorithms, for example, tracking notch filters.